Filter Bandpass Mikrostrip X-band Untuk Radar Cuaca - Gandaria Gandaria; Dharu Arseno; Edwar Edwar (eProceedings of Engineering, 2019)
Abstrak Filter merupakan perangkat yang penting untuk sistem microwave, salah satu contohnya pada radar. Pada radar, filter terdapat dalam blok sistem yang berfungsi untuk meredam sinyal-sinyal pada frekuensi yang tidak diinginkan dan meloloskan sinyal pada frekuensi yang diinginkan. Perancangan filter disesuaikan dengan frekuensi kerja dan dimana filter tersebut akan digunakan. Pada tugas akhir ini dirancang dan disimulasikan filter bandpass mikrostrip yang bekerja pada frekuensi X-band dengan contoh aplikasinya pada radar cuaca sehingga dibutuhkan filter dengan dimensi yang cukup kecil namun dengan kinerja yang bagus pula. Filter dirancang dengan menggunakan tiga jenis resonator berbasis square diantaranya square loop resonator, square open loop, dan meander. Substrat yang digunakan yaitu RT Duroid 5880LZ dengan konstanta dielektrik sebesar 2 dan tebal substrat 1,27 mm. Berdasarkan simulasi hasilnya yaitu nilai return loss filter square loop resonator -14,1524 dB, filter square open loop resonator sebesar -13,679 dB, dan filter meander sebesar -21,139 dB. Nilai insertion loss filter square loop resonator sebesar - 2,2875 dB, filter square open loop resonator sebesar -2,44 dB, dan filter meander sebesar -1,386 dB. Bandwidth filter square loop resonatorsebesar 299 MHz, filter square open loop resonator sebesar 301 MHz, dan filter meander sebesar 300 MHz. Semua filter mempunyai frekuensi tengah di 9 GHz. Kata Kunci : bandpass filter, mikrostrip, square loop resonator, square open loop, meander. Abstract Filter is an important component for microwave systems, one of the example is the radar system. In the radar system, the filter located in the block system for attenuates the undesired signals at the certain range of frequency and passes the desired signals at the certain range of frequency. Design of filter depends on working frequencies and the location where the filter will be used. This final project designs microstrip bandpass filter that works at X-Band frequency, with an example application on the weather radar so the filter has to be design in small dimensions but with a great performance. The filter will be designed using three type of resonators based on square shape including square ring, square open loop, and meander. The substrate material used in this final project is RT Duroid 5880LZ with the value of dielectrict constant is 2 and substrate thickness is 1,27 mm. Based on the simulations, the values of return loss from square loop filter is -14,1524 dB, square open loop filter is -13,679 dB, and meander filter is -21,139 dB. The values of insertion loss from square loop filter is -2,2875 dB, square open loop filter is -2,44 dB dB, and meander filter is -1,386 dB. The values of bandwidth from square loop filter is 299 MHz, square open loop filter is 301 MHz, and meander filter is 300 MHz. All of the filters has center frequency at 9 GHz. Keywords : bandpass filter, microstrip, square loop resonator, square open loop, meander.